Anatomi Humor Drama Tradisional Rudat di Lombok - Qodri, Muh. Syahrui; Khairussibyan, Muh.; Jafar, Syamsinas; Ramdhani, Marlinda (SULUK : Jurnal Bahasa, Sastra, dan Budaya, 2024)
This research focuses on humor in the Rudat Temu Karya performance in southern East Lombok. Most previous studies only studied the story and value aspects of traditional Lombok drama performances, but failed to examine the aspect that is the main attraction for audiences, namely the humor aspect. Based on Berger's humor theory which divides humor techniques into four categories, namely language, logic, identity and action, this research examines the anatomical aspects of traditional Lombok drama humor which relate to the socio-cultural context of Lombok society. The data in this research was collected using interview and documentary methods. The results of this research show that the variations of techniques that are widely used are various humor techniques which include humor in language categories such as ridicule, theme and variations, insults, and puns (play on words). The most dominant technique used is the slapstick technique (rough jokes/jokes) which is included in the action category. Research on this aspect of humor shows that socio-cultural aspects influence the success of humor in rudat Temu Karya performances.